2021
DOI: 10.3390/biology10050359
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Biomarkers and Therapeutic Tools: From Pre-Clinical to Clinical Applications

Abstract: Extracellular vesicles (EVs) are ubiquitous masters of intercellular communication, being detectable in tissues, circulation, and body fluids. Their complex cargo reflects the (patho)physiologic status of the cells from which they originate. Due to these properties, the potential of EVs, and in particular exosomes, to serve as biomarkers or therapeutics has grown exponentially over the past decade. On one side, numerous studies have demonstrated that EV-associated nucleic acids and proteins are implicated in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 77 publications
0
91
0
Order By: Relevance
“…It is known that EVs are vehicles of intercellular communication involved in many (patho) physiological processes. Moreover, these qualities joined to their molecular composition have positioned EVs as one of the most stable options for diagnostic and therapeutic purposes [ 34 ]. According to our data, phase F, which is the one harboring all exosomes, contains all mitochondrial markers totally stable in blood with significances among patients and controls, which makes them potential non-invasive biomarkers for RCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that EVs are vehicles of intercellular communication involved in many (patho) physiological processes. Moreover, these qualities joined to their molecular composition have positioned EVs as one of the most stable options for diagnostic and therapeutic purposes [ 34 ]. According to our data, phase F, which is the one harboring all exosomes, contains all mitochondrial markers totally stable in blood with significances among patients and controls, which makes them potential non-invasive biomarkers for RCC diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This diverse group of biological carriers participates in various physiological and pathophysiological processes, which sparked scientific interest in recent years. Aside from being useful diagnostic and Membranes 2021, 11, 647 2 of 13 prognostic tools, which can be obtained with minimally invasive techniques [5], EV are increasingly seen as potentially privileged drug carriers [6]. Their small size and lipid bilayer confer EV the ability to travel long distances in the body, including crossing the blood-brain barrier [7] without disturbing their cargo.…”
Section: Introductionmentioning
confidence: 99%
“…Recent published studies suggest that EVs can be used as a prognostic/diagnostic tool for several diseases and as a therapeutic approach [70][71][72][73][74]. At the same time, it was demonstrated that cancer cells can use EVs as a mechanism to expulse chemotherapy drugs, contributing to drug resistance [75,76].…”
Section: Extracellular Vesiclesmentioning
confidence: 99%